Formulation of ophtalmic vitamin A nanoemulsion with Kolliphor® EL as surfactant and transcutol as cosurfactant and hen’s egg test chorioallantoic membrane (HET CAM) irritation test - Fatmawati Fatimah Siti; Saras Sukmaningrum Galuh; Vanda Pertiwi Deasy; Efiana Nuri Ari (BIO Web of Conferences)
Conventional eye drop preparations are the main choice for the treatment of eye disorders; however, they have low penetration and bioavailability. Vitamin A is nonphotostable, lipophilic, and easily degraded in the presence of oxygen. This study aimed to characterize a vitamin A ophthalmic nanoemulsion without any irritation. The nanoemulsion was prepared using a mixture of surfactant Kolliphor® EL and cosurfactant Transcutol (Smix) for F1 (1:1), F2 (1:2), and F3 (2:1). The formulas were examined by pH, optical transmission, refractive index, particle size, PDI, and Hen’s Egg Test Chorioallantoic Membrane (HET-CAM) irritation tests. The selected formula was F3, with the best optical transmission (97.35 ± 0.173%), pH (4.94 ± 0.04), refractive index (1.3534 ± 0.0002), particle size (24.47 ± 1.888 nm), PDI (0.353 ± 0.02), and no irritation response. This formula shows a good potential for ophthalmic eye drop preparation.